WEBSITE PEMESANAN PENGINAPAN DI PALANGKA RAYA - Adi Novari Chandra; Felicia Sylviana; Nahumi Nugrahaningsih (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Internet as a means of fast and easy information media for the general public, in this case can also be used to find accommodation in Palangka Raya, Website booking accommodation in Palangka Raya also to facilitate customers in the process of booking a stay where customers can know the availability of room, room facilities and last room price also make it easier for the property to use it as a media information on the The property can manage the accommodation, rooms, room facilities as well as confirmation of orders from customers, then admin tasks as the manager of the website. The method of software development used is the advanced waterfall methodology, namely analysis, design, coding and testing. At the analysis stage, there was an analysis of old systems and new systems and analysis of databases using the DFD methodology after that design. In testing stage using Black Box testing method, which is a testing strategy that focuses solely on the functionality factor and software specifications. Suggestion for development of this website by adding filtering feature with map concept based on route or nearby location.